Pemberdayaan Kader dan Keluarga dalam Pengelolaan Diabetes Melitus di RW 2 Kelurahan Kampung Bugis - romalina, Romalina; Daniati, Meisa; Erda, Zulya; Suriani, Yas (SEGANTANG LADA : JURNAL PENGABDIAN KESEHATAN, 2025)
The national health transformation program requires support from various stakeholders, including educational institutions such as Poltekkes of the Ministry of Health in Tanjungpinang. Data from the Kampung Bugis Health Center shows an increase in Diabetes Mellitus (DM) cases, rising from the fifth to the fourth most common disease between 2022 and 2023, with many patients presenting with complications. This community service activity aimed to improve the knowledge of health cadres, DM patients, and their families regarding DM management. The methods included health education on DM awareness, treatment, and dietary management, as well as blood glucose screening. Knowledge was assessed using pre- and post-tests involving 30 participants. The results showed an increase in knowledge from 87% categorized as good in the pre-test to 100% in the post-test. This activity proved effective in enhancing participants’ understanding of DM management.